Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T17:59:36+01:00
Metoda przeciwnych współczynników:
a)
x + 3y=11
2x - y=8 /x3

x + 3y=11
6x - 3y=24

7x=35/:7
x=5


x + 3y=11 /x (-2)
2x - y=8

-2x-6y=-22
2x-y=8

-7y=14/: (-7)
y=-2

b)
3x-5y=7
x+y=-3 /x (-3)

3x-5y=7
-3x-3y=9

-8y=16 /: (-8)
y=2


3x-5y=7
x+y=-3 /x5

3x-5y=7
5x+5y=-15

8x=8 /:8
x=1

Metoda podstawiania:
b)
3x-5y=7
x+y=-3

x=-y-3
3(-y-3)-5y=7

-3y-9-5y=7
-3y-5y=7+9
-8y=16 /:(-8)
y=2



3x-5y=7
x+y=-3

y=-3-x
3x-5(-3-x)=7

3x+15+5x=7
3x+5x=7-15
8x=8 /:8
x=1

a)
x + 3y=11
2x - y=8

x=11-3y
2(11-3y)-y=8

22-6y-y=8
-7y=8-22
-7y=14 /:7
y=-2

x + 3y=11
2x - y=8

-y=8-2x /: (-1)
x+3y=11

y=-8+2x
x+3(-8+2x)=11

x-24+6x=11
x+6x=11+24
7x=35 /:7
x=5


Proszę :)